Extended inverse compton emission from distant powerful radio galaxies - Erlund, M; Fabian, A; Blundell, K; Celotti, A; Crawford, C (2006)
Chandra observations of 3C432, 3C 191 and B2 0902+34 are presented as part of an ongoing search for inverse-Compton scattering of the cosmic microwave background (CMB) from high redshift radio sources (Schwartz, 2000). The energy density of the CMB increases with redshift, z, as (1 + z)4, so the relatively high redshift of these powerful radio galaxies makes them good candidates for detecting extended inverse-Compton scattering along the radio jet axis: we do indeed detect radio-aligned X-ray emission.